Primary Teratoma of the Lesser Sac: Lesser Sac Teratoma. (25th March 2012) - Hardesty, Brandon M.; Ulbright, Thomas M.; Touloukian, Christopher; Einhorn, Lawrence H.
Abstract : Germ cell tumors predominantly involve the gonads but may rarely be found outside of the gonads, primarily in midline structures. We describe the case of a 27-year-old male with an asymptomatic 8 cm teratoma located within the lesser sac of his omentum. This is the fourth case of a teratoma located within the lesser sac of the omentum, which provides the opportunity to make some comparisons. Finally, we discuss some of the etiologic theories behind extragonadal germ cell tumors and how they relate to teratomas in the lesser sac.